The Phenomenology of Depression as a Modification of the Own Experience of the Self: Body Opacity, Temporal Desynchronization and Guiltiness - Martínez Lucena, Jorge (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
Last years, phenomenology has demonstrated its own value in the field of medicine with useful distinctions as the one among illness and disease. It has also contributed to psychiatry. Some inter-disciplinary works about mental illnesses can be found. The phenomenological description of the melancholic depression patient has three main features: a) the transformation of his own body experience; b) a continuous feeling of guilt; and c) a time experience which is desynchronized from the otherness. This paper aims to synthetize this phenomenological research about depression, which has been considered one of the plagues of our time. Moreover, it tries to explain how these changes in the patient’s experience can imply certain modifications of his own self-experience.